2022
DOI: 10.26689/jcnr.v6i6.4502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TRX Suspension Training on Physical Function in Elderly Men with Sarcopenia

Abstract: Elderly people have reduced muscle mass, decreased physical function and an increased hospitalization probability, which affect their quality of life and even lead to death in severe cases. Scholars at home and abroad have studied progressive body muscle loss associated with increase of age, decreased muscle strength and muscle function impairment syndrome and how to prevent them. Much research have been done preventing diseases and improving muscle strength through exercising, nutrition, and drug intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A total of 5 studies on total cholesterol were included [43,44,47,48,50] However, there was no significant difference in training therapy between any two groups (P > 0.05). The results of the best probability ranking showed that Pilates training had the best effect on reducing total cholesterol in diabetic patients with frailty.…”
Section: Total Cholesterolmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 5 studies on total cholesterol were included [43,44,47,48,50] However, there was no significant difference in training therapy between any two groups (P > 0.05). The results of the best probability ranking showed that Pilates training had the best effect on reducing total cholesterol in diabetic patients with frailty.…”
Section: Total Cholesterolmentioning
confidence: 99%
“…A total of 5 studies on triglycerides were included [43,44,47,48,50]. The results of network Meta-analysis showed that Pilates training [MD = − 0.86, 95%CI (− 1.37, − 0.33), 6, Additional file 1: Annexes 1).…”
Section: Triglyceridesmentioning
confidence: 99%
See 1 more Smart Citation